Evaluation of Pioglitazone Vildagliptin Combination on Lipid Profiles for Outpatients with Type II Diabetes Mellitus - Kusumaningrum, Yunita Dyah; Firandi, Adelia; Hasmono, Didik; Aryani, Dhita; Wardhani, Firdha Aprillia (Fakultas Farmasi Institut Kesehatan Medistra Lubuk Pakam, 2025)
Pioglitazone and vildagliptin combination is one of the recommended alternatives as antidiabetic therapy to achieve the therapeutic target. This combination with complementary mechanisms of action can improve lipid profiles. This study aims to evaluate lipid profile achievement for outpatients with Type II DM on administering pioglitazone/vildagliptin combination therapy. Methods of the study were an observational prospective study in outpatients with Type II DM who use pioglitazone/vildagliptin combination at RS. Bhayangkara Surabaya during November 2021 – April 2022. Patients were included if aged between 18-80 y.o, used this combination ? 3 months before the study, HbA1C >7%, and were voluntarily involved by signing the informed consent. Laboratory examination of HbA1c, HDL-C, and triglycerides was done initially when patients were voluntarily involved as baseline data and after 3 months as post-data. The final sample in this study consisted of 25 patients who met the inclusion and exclusion criteria. The results of the study show mean value of HDL-C significantly increases from baseline to endpoint (p < 0.05). At the end of 3 months, the lipid profile of HDL-C and triglyceride increases by 30% and 4%, respectively, in patients who achieve the target compared to baseline conditions. The combination therapy of pioglitazone and vildagliptin improved lipid profile control in patients with type 2 diabetes mellitus after 3 months of treatment.